Unethical Pro-Organizational Behavior: The Role of Moral Courage - Sawitri, Hunik Sri Runing; Mayasari, Desy; Ayuninggar, Lintang; Novela Q A, Intan; Harsono, Mugi (Management Analysis Journal, 2021)
Unethical pro-organizational behavior is defined as conduct that is deemed to contravene ethical standards as defined by widely held values, laws, and social conventions rather than by group or organizational norms. However, the behavior is intended to benefit the organization, members of the organization, or both. Employees who intend to help the organization, its members, or both often engage in unethical pro-organizational behavior. This research aimed to identify, test, and develop a model of the factors that encourage people to engage in unethical pro-organizational behavior. These factors include identification with supervisors (IS), taking responsibility (TR), transformational leadership (TL), identification with the organization (IO), and moral courage (MC). The study employed a survey method, and the main respondents comprised the heads of the study programs at Universitas Sebelas Maret (UNS) Surakarta. The results of the analysis employing the Smart-PLS demonstrated that identification with the organization and taking responsibility had significant effects on unethical pro-organizational behavior, while identification with supervisors did not significantly affect unethical pro-organizational behavior. Moral courage did not moderate (neither strengthen nor weaken) the effects of taking responsibility and identification with supervisor on unethical behavior. Then, transformational leadership had a significant effect on identification with the organization. Finally, identification with the organization mediated the effect of transformational leadership on unethical pro-organizational behavior.